Corrosion Behaviour of Steel/55% Al-Zn Alloy/Paint Systems Exposed to Natural and Artificial Environments - Elsner, Cecilia Inés (2014)
The corrosion performance of steel/55%Al–Zn alloy sheets pre‐treated with 5% Fe (NO3)3þ15% H3PO4 solution, and then coated with acrylic (AC), alkyd (AQ), vinyl (VL), solvent‐based epoxy (ES) or waterborne epoxy (EA) corrosion‐inhibiting primersþa barrier topcoat alkyd paint was studied. Exposure conditions included weathering chambers and natural atmospheres (La Plata‐Argentina and San Luis‐Potosí, México). The panels' behaviour was evaluated through visual inspections and EIS measurements. Their results allowed inferring that: (1) most of the painting systems have a satisfactory performance during their exposure to the accelerated weathering chamber or the natural atmospheric stations and (2) the correlation between them allowed explaining some problems arising in service. This information will allow extending the useful life by adjusting the painting system formulation.